Adsorption of Ferricyanide Ion onActivated Carbon and γ-Alumina - J. Ketcha Mbadcam; G. F. Tchatat Wouaha; V. Hambate Gomdje (E-Journal of Chemistry)
Iron-cyanide complexes are present in soil and ground water due to anthropogenic inputs. We compared the adsorption of ferricyanide ion, on two commercial activated carbons (COM3 and COM4) and γ-alumina (A1G) in aqueous solution. Isotherm parameters obtained from batch experiments of iron-cyanide complex adsorption on these adsorbents were carried-out. The mass of the adsorbents were varied at 40 mg, 60 mg and 100 mg and the inorganic ion initial concentrations, Co also varied between 3.04×10-4 and 2.43×10-3 mol/L. The equilibrium data obtained were tested by using the Langmuir and Freundlich isotherm models. These data fit well with the Langmuir and Freundlich isotherm models at this low inorganic ion initial concentration.